A new method for ultrasonographic measurement of kidney size in healthy dogs() - Barella, G. (Elsevier, 2012)
INTRODUCTION: The authors propose a simple method for assessment of canine kidney size derived from the radiological technique described by Finco et al in 1971. MATERIALS AND METHODS: In 26 healthy dogs ultrasonography was used to measure the length, height, and thickness of each kidney. These measurements were correlated with the lengths of the fifth and sixth lumbar vertebrae (L5 and L6), also measured by ultrasound. The resulting values were compared with the linear correlation method and the ratios defined using descriptive statistics. RESULTS: No significant differences were observed between the dimensions of the right and left kidneys. The length of both kidneys displayed significant correlation with both the length of L5 and that of L6. In both cases, the renal:vertebral length ratios ranged from 1.3 to 2.7. DISCUSSION: The ratio of kidney length to the length of L5 or L6 can be considered a useful parameter for assessing the size of the kidneys in healthy dogs. The normal range we identified in this study (from 1.3 to 2.7) is sufficiently narrow to allow sonographic detection of even limited changes in renal length.